PEMBINAAN ROHANI ORANG TUA MURID MENDAMPINGI ANAK DALAM BELAJAR DI GEREJA BETHEL INDONESIA TAMAN LAGUNA INDAH - Suhartono, Tony; Suriyanti, Intan; Gulo, Fitriyani; Situmorang, Maruba (JURNAL BEATITUDES, 2024)
The role of parents is very important in educating and teaching their children. There are many things that parents can do in educating and teaching their children so that children become better and achieve. However, there are also problems in teaching and educating children. For this reason, the Tabgha Batam Theological College (ST3B) Christian Religious Education study program conducts Community Service (PkM) in the form of guidance and counseling for parents at the Bethel Indonesia Church (GBI) Taman Laguna Indah Sekupang with the theme "Spiritual Development of Parents of Students Accompanying Children to Learn" on Sunday, July 7, 2024. The implementation of PkM is in the form of lectures, providing examples and the implementation of questions and answers between the parents present and the lecturers who carry out the PkM. The role of parents in supporting children's learning achievement is to nurture, educate, guide, accompany, motivate (Motivator) and be a facilitator. Children who follow directions and get more guidance, teachings, and facilities from their parents will be better at learning.